Answer:
Option A - ( 5 + 6 ) + 7 = 5 + ( 6 + 7 )
Explanation:
In this question we are asked about which expression shows that
11 + 7 = 5 + 13
For this, the answer will be
Option a that is ( 5 + 6 ) + 7 = 5 + ( 6 + 7 )
Because ( 5 + 6 ) = 11
Then +7 at the other side 5 add with ( 6 + 7 ) that is equal to 13,
This is the method we do step by step,
First ( 5 + 6 ) is 11
Then another side ( 6 + 7 ) = 13
Then we add 11 with 7 and another side 5 with 13,
Therefore, option a ( 5 + 6 ) + 7 = 5 + ( 6 + 7 ) is the right answer